Local revenue and fiscal independence: a strategic role in the development of South Sumatra Province - Amirah Andika Rifdayanti (Jurnal Mantik, 2023)
This study aims to analyze the strategic role of regional original revenue in achieving fiscal independence in the South Sumatra Province. This study utilizes a qualitative descriptive approach by analyzing secondary data collected from the Central Statistics Agency of the South Sumatra Provincial Government and other reliable sources. The data includes information on the condition of regional original revenue, dependency on the central government, and efforts made to enhance fiscal independence. The research findings indicate that the regional original revenue of South Sumatra Province still significantly relies on support from the central government, such as general allocation fund and special allocation fund. There is an urgent need to enhance regional original revenue in order to achieve fiscal independence. Local taxes and levies are the main sources of regional original revenue, and optimal management of local taxes can contribute to increasing regional original revenue. Recommended efforts include improving the management of local taxes, raising awareness and imposing strict sanctions in tax collection, and increasing revenue from other potential sectors. In conclusion, the increase in regional original revenue plays a strategic role in achieving fiscal independence. Optimizing the management of local taxes and diversifying sources of revenue are crucial steps to reduce dependency on the central government and strengthen local finances.